Promoting protean career through job-related factor: career strategies as moderator - Wong, Siew Chin; Mohd Rasdi, Roziah (Australian Academy of Business and Social Sciences, 2015)
The study used the partial least squares (PLS) tool to examine job-related factors influencing protean career behaviour among employees. It also measures the impact of career strategies as a moderator in protean career relationships. Quantitative data was collected from 306 full time employees in the Malaysia. Statistical results confirm that job autonomy and job feedback (i.e., job-related factor) have significant impact on protean career. Job-related variables are viewed as potential predictors of protean career. However, there is no significant moderating effect of career strategies on the relationship between job autonomy and job feedback and protean career. Findings are useful for HRD practitioners to develop relevant HRD interventions to assist individuals and organisations towards protean career behaviour development. Limitations and suggestions for future research are also included.